ANALISIS MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDI KASUS PT INDOFOOD SUKSES MAKMUR,TBK) - Nurkurniana Nurkurniana (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
This research is based on the existence of company internal issue that the ability of obtaining profit can be seen from the growth of company’s profitability. The growth of profitability from year to year has degraded shows the unstable company on obtaining profit so it is important to know if management of working capital can improve company profitability.This study is a quantitative research that will provide data in the form of numbers or ratio about the analysis of working capital on profitability at manufacturing companies listed on the Indonesia Stock Exchange. Method of data collection in this research is observation and document of research subject.The results of this study can be seen that the management of working capital can increase profitability significantly.